Utility and safety of the MANTA device for access site closure after removal of the mechanical hemodynamic support device Impella on the intensive care unit. (14th October 2021) - Burkart, P; Bossard, M; Moccetti, F; Hess, S; Jeyarasa, M; Madanchi, M; Cioffi, G; Seiler, T; Wolfrum, M; Hakimi, M; Seelos, R; Toggweiler, S; et al.
Abstract: Background: The percutaneously implanted hemodynamic mechanical support devices Impella are commonly used in patients at risk for or with cardiogenic shock (CS). Impella removal after hemodynamic stabilization on the intensive care unit (ICU) remains a major challenge and is prone to high rates of bleeding and vascular complications. Purpose: It is unknown if the use of the novel large-bore access closure device MANTA® is safe and facilitates access management compared to manual compression. Methods: Between January 2017 and December 2020, 172 CS patients were treated with an Impella® device at our centre. Of those, in 89 patients the Impella® was removed on the ICU and access site management occurred with either MANTA® device or manual compression. The criteria for MANTA® 14 french device deployment included: (i) femoral artery Diameter >6mm and (ii) absence of significant peripheral arterial disease (PAD). Bleeding and vascular access site complications were assessed and adjudicated according to the Valve Academic Research Consortium-2 (VARC-2) criteria. Results: Among the 89 included patients, Impella® removal was performed using the MANTA® device in 31 cases and manual compression in 58 cases. Mean age was 66±11 years, and 50 (56.2%) patients had a CS classified as Society for Cardiovascular Angiography and Interventions (SCAI) D or higher due to myocardial infarction. Median support time was 40 (IQR 24; 69) hours. Baseline characteristics are displayed in Table 1. Immediate haemostasis was more frequently achieved by MANTA® device compared to manual compression (p=0.034). Moreover, we observed significantly less overall (2 (6.5%) vs. 22 (37.9%), p=0.001) and minor bleedings (1 (3.2%) vs. 15 (25.9%), p=0.006) with the MANTA® device when compared to manual compression. Of note, there were no significant differences in vascular complications between the two groups (Table 2). Conclusions: In patients requiring Impella® support and residing on ICU, the MANTA® device, compared to standard of care manual compression, seems to be a safe and effective option for access site management, especially with regards to the reduction of bleeding events. However, physicians should carefully assess the vascular anatomy and degree of calcification prior to deployment of the MANTA® device. Nevertheless, more prospective data is necessary for evaluating the optimal access closure among CS patients treated with a percutaneously implanted Impella® device. FUNDunding Acknowledgement: Type of funding sources: None.